IMPLEMENTATION OF A FUZZY ADAPTIVE PI REGULATOR ON AN S7-300 INDUSTRIAL PROGRAMMABLE CONTROLLER IN VIEW OF THE SPEED CONTROL OF AN ASYNCHRONOUS MACHINE (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This article presents the design and implementation of an adaptive-fuzzy PI controller in a SIEMENS S7-300 Programmable Logic Controller in order to improve the performance of the internal PID controller of the PLC. The inputs of the adaptive-fuzzy PI regulator are the adjustment error e(t) and its variation . They are chosen to represent as faithfully as possible the dynamics of the system. The outputs of the fuzzy regulator are connected to the PID regulator of the PLC in order to adapt its gains Kp and Ti using the techniques of fuzzy logic theory. This adaptive-fuzzy PI regulator is used to control in closed loop the speed of an MAS via a VFD variable frequency drive. On the other hand, the scalar control is chosen at the level of the VFD to carry out this regulation. A validation test is carried out in order to compare the results of the designed regulator, obtained by means of the PLCSIM simulator with those obtained by the fuzzy module designed under Matlab. The experimental results obtained show the difference between the performances of PI and PI-fuzzy regulators. By using the fuzzy PI regulator, the response time was reduced to 50% compared to that obtained by the classic PI regulator.
Keywords: Programmable logic controller; Asynchronous machine; Proportional-integral controller; Proportional-integral adaptive-fuzzy,; Fuzzy logic; Variable frequency drive